Psoriasis: Immunological and genetic blueprints driving pathogenesis and potential for personalized therapies - Mohamed J. Saadh; Omer Qutaiba B. Allela; Radhwan Abdul Kareem; Gaurav Sanghvi; G. Padma Priya; Rishabh Thakur; Mukesh Kumari; Sofia Gupta; Kakhramon Khaitov; Hayder Naji Sameer; Ahmed Yaseen; Zainab H. Athab; et al. (Iranian Journal of Basic Medical Sciences, 2025)
Psoriasis is a long-lasting inflammatory skin condition that impacts millions globally. The occurrence of this disorder differs significantly across various areas, resulting from a complex interplay of genetic and environmental influences. In psoriasis, the pathogenesis represents a complex interaction of innate and adaptive immunity that plays a significant role in the disease manifestation process. Many genetic factors predispose to psoriasis, which is considered a polygenic disease. Several genes concerning pathways like NF-κB and PI3K/Akt that modulate the amplification of inflammatory response and keratinocyte dysregulation have been elaborated in the light of their differential expression, susceptibility loci, and polymorphisms. Such genetic insights could open a whole new avenue for precision medicine in which biomarkers and gene-targeting therapies are promising options for personalized treatment. This review emphasizes the need for complex investigations into psoriasis, from molecular mechanisms to clinical manifestations, to bridge the gap between basic research and therapeutic development by furthering the understanding of psoriasis and paving the way for innovative treatments addressing skin lesions and systemic effects.